Determination Education, Health Training, Flexibility and Experience on Adaptability of Health Workers: Study at UPT Puskesmas Rumbio - Akmal, Saidatul; Marantika, Abshor; Zulher, Zulher (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The effectiveness of this policy not only depends on the readiness of the technological infrastructure, but is also greatly influenced by the adaptability of health workers in responding to changes in systems, work procedures, and the increasingly complex dynamics of community needs.  Study This aim for evaluate influence education and training, flexibility, and experience Work to level adaptability power health at the Community Health Center UPT Rumbio. Study This use approach quantitative with Structural Equation Modeling (SEM) method. Respondent study consists of of 44 workers health workers working in the UPT Puskesmas environment Rumbio. Research results show that: (1) education and training proven give influence positive and significant to adaptability; (2) flexibility No show significant influence​ to adaptability; and (3) experience Work contribute positive and significant in increase adaptability power health. With thus, it can concluded that education, training, and experience Work own a bigger role dominant in form ability adaptation compared to flexibility individual. Because that, is necessary effort sustainable from agency health for strengthening training-education programs and providing more opportunities​ wide for power health in develop experience work. This strategy expected capable push improvement ability adaptation power health to dynamics changes in the sector service health.